Influence of partial substitution of dietary marine origin feedstuffs by a mixture of extruded pea seed meal and animal origin feedstuffs on fatty acid composition of fillet in sea bass (Dicentrarchus labrax). Issue 4 (1st October 2016) - Scerra, Manuel; Foti, Francesco; Caparra, Pasquale; Cilione, Caterina; Violi, Laura; Lamanna, Piero; Chies, Luigi
Abstract: The aim of the study was to investigate how partial replacement of marine origin feedstuffs by a mixture of terrestrial origin (extruded pea meal, feather meal, spray-dried blood meal, soybean oil) feedstuffs affects the fatty acid composition of European sea bass fillet. Two experimental diets were formulated for the better growth of sea bass with an initial mean weight of 30 g in sea cages placed at 2500 m from the coast. The marine diet (MD) diet included 45% of marine origin feedstuffs, containing 30% of fish meal (herring), 10% of fish oil (anchovy) and 5% of krill meal, while terrestrial diet (TD) diet included 20% less of marine origin feedstuffs replaced by a mixture of terrestrial origin feedstuffs. The experimental diets did not affect growth performance and food conversion ratio in sea bass. The contents of EPA and DHA resulted lower in tissues of fish fed diet with the higher levels of terrestrial origin feedstuffs. Consequently, also the levels of total n-3 PUFA were lower in muscle of fish of this group; conversely total n-6 PUFA resulted in higher levels. According to the effect of treatments on both total n-6 and n-3 PUFA, the ratio of ∑n-6/∑n-3 FA was higher in fillet of sea bass fed TD diet, maintaining anyway values sufficiently acceptable for a healthy diet according to Brennal et al.